A slip boundary condition of fluid flow through microchannel - Yu, Guang Ning. (2010)
Recent years, micro scale system becomes more and more popular; this kind of system involves micro flow as a very important part. These flows do not behave like conventional flows and classical theories are unable to describe them. Therefore many groups of researchers are doing a lot of studies on them. Up till now there are still a lot of aspects, including boundary conditions, of micro flows that need to be studied on. In order to predict slip velocity of micro flows, Maxwell’s first-order slip boundary condition is formulated. It is very simplified and widely used. However, this prediction is not accurate to certain extents. The aim is to review the experimental studies regarding measurement of slip length, to define the surface force different between slip boundary condition and non-slip boundary condition, and to make an improvement on the slip boundary condition by incorporating micro-rotations in the derivation. Based on a few assumptions, the new formulation takes on the same form as Maxwell’s slip boundary condition with additional terms and can be seen as an extension of the latter. It is recommended to work further on this new formula and verify if it is conforms more to the experimental results. More studies can be done by considering different scenarios of fluid flows.